2007
DOI: 10.1111/j.1365-2265.2007.02775.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary aldosteronism: renaissance of a syndrome

Abstract: Great strides have been made in our understanding of the pathophysiology of primary aldosteronism syndrome since Conn's description of the clinical presentation of a patient with an aldosterone-producing adenoma (APA) more than 50 years ago. It is now recognized that the APA is just one of the seven subtypes of primary aldosteronism. APA and bilateral idiopathic hyperaldosteronism (IHA) are the most common subtypes of primary aldosteronism. Although most clinicians had thought primary aldosteronism to be a rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
486
4
28

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 586 publications
(527 citation statements)
references
References 101 publications
6
486
4
28
Order By: Relevance
“…The ARR [ALD (ng/dL)/PRA (ng/mL/hour)] and the ARC [ALD (ng/dL)/PRC (pg/mL)] were calculated in hypertensive patients, ARR values were considered suspicious for PA only with ALD ≥ 15 ng/dL, in agreement with other authors (8,9).…”
Section: Assay Methods and Measurementssupporting
confidence: 69%
See 1 more Smart Citation
“…The ARR [ALD (ng/dL)/PRA (ng/mL/hour)] and the ARC [ALD (ng/dL)/PRC (pg/mL)] were calculated in hypertensive patients, ARR values were considered suspicious for PA only with ALD ≥ 15 ng/dL, in agreement with other authors (8,9).…”
Section: Assay Methods and Measurementssupporting
confidence: 69%
“…PA was confirmed with ALD levels above 6 ng/dL in the FST (10) and above 7 ng/dL in the SIT (11). In all PA patients, adrenal computed tomography was obtained, and in two of them (1 adenoma and 1 hyperplasia) adrenal venous catheterization was performed (9).…”
Section: Assay Methods and Measurementsmentioning
confidence: 99%
“…7 Therefore, in the diagnosis of PA, hypokalemia has low sensitivity and specificity and is not anymore suggested as a criterion to make the diagnosis of PA. 1,8 The plasma aldosterone-to-plasma renin activity (A PL /PRA) ratio has proved to be one of the most reliable parameters in the screening for PA. Many studies have shown superior sensitivity and specificity of the A PL /PRA ratio, as compared with measurements of A PL or renin alone.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to what is observed in humans, in which the primary bilateral idiopathic hyperaldosteronism (60-65% of cases), and aldosterone secretory adenoma (30-35% of cases) represent the majority of cases (YOUNG, 2003;YOUNG, 2007), in cats, hyperaldosteronism is mostly attributed to adenomas or adenocarcinomas of adrenal glands (DJAJADININGRAT-LAANEN et al, 2011). Of 25 cases in cats with histopathological confirmation described in the literature, 13 were related to carcinoma, seven to unilateral adenomas, two to bilateral adenomas and three to bilateral hyperplasia (DJAJADININGRAT-LAANEN et al, 2011).…”
Section: Etiology and Pathophysiology Of Hyperaldosteronismmentioning
confidence: 73%